2010
DOI: 10.2215/cjn.03380410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Add-on Fluvastatin Therapy in Patients with Chronic Proteinuric Nephropathy on Dual Renin-Angiotensin System Blockade

Abstract: Background and objectives:This open, prospective, randomized trial aimed to assess the effects of statins in chronic kidney disease patients on optimized antiproteinuric treatment with combined angiotensin-converting enzyme inhibition and angiotensin receptor blockade.Design, setting, participants, & measurements: After 1-month benazepril therapy followed by 1-month benazepril-valsartan combined therapy (run-in), 186 consenting patients with residual proteinuria >0.5 g/24 h were randomized to 6-month benazepri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 36 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Patients were all then maintained on dual RAS inhibitor therapy and prospectively followed-up. Their GFR decline over the following 6 years was significantly slower than in matched reference patients receiving single drug RAS blockade with full dose of an ACE inhibitor 75 More recently, the ESPLANADE trial 76 showed that, in 186 patients with chronic proteinuric nephropathies, the larger reduction in proteinuria achieved by combined therapy with benazepril and valsartan compared with benazepril alone, was associated with concomitant reduction in total, LDL, and HDL cholesterol, and apoB and apoA levels, an effect that in the long term might translate into reduced cardiovascular risk.…”
Section: Ace Inhibitors Arbs or Both?mentioning
confidence: 98%
See 1 more Smart Citation
“…Patients were all then maintained on dual RAS inhibitor therapy and prospectively followed-up. Their GFR decline over the following 6 years was significantly slower than in matched reference patients receiving single drug RAS blockade with full dose of an ACE inhibitor 75 More recently, the ESPLANADE trial 76 showed that, in 186 patients with chronic proteinuric nephropathies, the larger reduction in proteinuria achieved by combined therapy with benazepril and valsartan compared with benazepril alone, was associated with concomitant reduction in total, LDL, and HDL cholesterol, and apoB and apoA levels, an effect that in the long term might translate into reduced cardiovascular risk.…”
Section: Ace Inhibitors Arbs or Both?mentioning
confidence: 98%
“…it/remission/) and applied to all CKD patients with heavy proteinuria despite therapy. 75 This multimodal intervention strategy included lifestyle modifications such as sodium 93 and protein 30 intake restriction, smoking cessation, body weight loss, 94 optimal BP (target systolic/diastolic ,130/80 mmHg) and metabolic control (target hemoglobin A1C ,7.5%) in patients with diabetes, correction of metabolic acidosis 95 and hyperphosphatemia, 96 use of statins, 76,97,98 and dual RAS blockade with maximum tolerated doses of ACE inhibitors and ARBs, probably the mainstay of proteinuria management in this setting. 99 In a matched-cohort study, we compared the outcome of 56 CKD patients receiving the Remission Clinic approach because of persistent 24-hour proteinuria .3 g despite standard antihypertensive doses of an ACE inhibitor with that of 56 matched historical reference patients who had received ACE inhibitor therapy titrated to target BP.…”
Section: The Remission Clinic Examplementioning
confidence: 99%
“…22 In light of these findings, all attempts have been made to reduce proteinuria by any therapeutic means, including RAAS-blocking agents, low salt intake, 44 smoking cessation, optimal metabolic control, and 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors. 45 Multiple therapies aimed at reducing proteinuria may slow the progression of kidney disease to a greater extent than any single treatment. This was demonstrated effectively by a multimodal intervention strategy, the Remission Clinic program, that used all available lifestyle recommendations and pharmacologic tools to further reduce proteinuria in patients with CKD and severe proteinuria already treated with RAAS-blocking agents.…”
Section: Proteinuria: the Second "P" For Ckd Progressionmentioning
confidence: 99%
“…Taylor and coworkers (38) also reported on the ARBITER 6-HALTS trial (Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol 6-HDL and LDL Treatment Strategies) that addition of ezetimibe was no more effective compared with niacin in decreasing the progression of carotid intima-media thickness in patients receiving statin therapy ( Table 7). The Statins in Proteinuric Nephropathies (ESPLANADE) study assessed the effect of fluvastatin plus angiotensinconverting-enzyme inhibitors or angiotensin II receptor blockers in reducing proteinuria in patients with CKD and diabetic nephropathy (39). Patients were randomized to fluvastatin versus placebo and were followed for 6 months.…”
Section: Statins In Ckdmentioning
confidence: 99%